A Horizontally Polarized Omnidirectional Antenna Based on Spoof Surface Plasmons - Liao, Zhen; Luo, Guo Qing; Wu, Xin Yu; Cai, Ben Geng; Cao Pan, Bai; Pan, Yu Jian (Frontiers in Physics, 2020)
As an analog of the role of surface plasmons in optical antenna, spoof surface plasmons enable far-field radiation of antenna in microwave frequency. Here, a plasmonic metamaterial supporting spoof surface plasmons is experimentally demonstrated for horizontally polarized omnidirectional radiation in the microwave region. A simple and intuitive working principle in the spoof surface plasmonic metamaterial design is provided, along with full-wave simulations that agree well with the experimental results. The low profile and compact design with the omnidirectional radiation pattern promise a wide range of applications, such as ceiling antennas, surface-mounted indoor antennas and automobile antennas in microwave and radio frequencies.